'Serious' Disaster Video Games: An Innovative Approach to Teaching and Learning about Disasters and Disaster Risk Reduction. Issue 5 (2nd September 2020) - Gampell, Anthony; Gaillard, J. C.; Parsons, Meg; Le Dé, Loïc
Abstract: Scholars, practitioners and educators propose video games as innovative teaching methods to engage geography students. A methodological framework, informed by constructivist learning theory, explored the ability of 'serious' disaster video games to foster student participation in learning within four New Zealand schools. The findings indicate the utilization of video games within the classroom requires further consideration of the teaching and learning processes for both teachers and students. Ultimately, the alignment of video games to constructivism and pedagogical mechanisms of social science suggests the ability of geography to enable deeper discussions and engagement of the curriculum by both students and teachers.